Pengukuran Sentimen Sosial Terhadap Teknologi Kendaraan Listrik: Bukti Empiris di Indonesia - Atha Fitrah Riyadi; Faiz Ramadhani Rahman; Muhammad Aldiansyah Nofa Pratama; Muhammad Khanif Khafidli; Harry Patria (EXPERT: Jurnal Manajemen Sistem Informasi dan Teknologi, 2021)
Currently, climate change due to global warming is a concern for many parties. The greenhouse gas emissions level is increasing day by day. The major contributors to Air pollution are the greenhouse effect. Transportation accounts for about 27% of air pollution, and governments in various countries use electric vehicles to reduce air pollution. However, the success of using electric vehicles is depending on perception, people’s sentiment, and understanding. The main purpose of this research is to find out how public sentiment towards electric vehicles is through tweets and comments on the Twitter social media platform using sentiment analysis. The data obtained are 1084 tweets and comments. The data were classified using the Naïve Bayes method, K-Nearest Neighbor, and Decision Tree. The results showed that the Naïve Bayes Classification Method gave better results than K-Nearest Neighbor, and Decision Tree with an accuracy rate of 94% positive sentiment by 53%, negative sentiment by 38%, and neutral sentiment by 9%. So, it can be concluded that public sentiment towards electric vehicles is quite good based on conversations on the Twitter social media platform. In addition, the author also visualizes the results of the analysis in the form of graphs and word clouds so that they can help the electric vehicle industry players to understand public sentiment better and more accurately.